Sonodynamic therapy-based nanoplatforms for combating bacterial infections - Xu, Pei-Yao; Kumar Kankala, Ranjith; Wang, Shi-Bin; Chen, Ai-Zheng (Ultrasonics sonochemistry, 2023)
•Various types of nanoplatforms for SDT are introduced.•The applicability of SDT-based antibacterial strategies are reviewed. The rapid spread and uncontrollable evolution of antibiotic-resistant bacteria have already become urgent global to treat bacterial infections. Sonodynamic therapy (SDT), a noninvasive and effective therapeutic strategy, has broadened the way toward dealing with antibiotic-resistant bacteria and biofilms, which base on ultrasound (US) with sonosensitizer. Sonosensitizer, based on small organic molecules or inorganic nanoparticles, is essential to the SDT process. Thus, it is meaningful to design a sonosensitizer-loaded nanoplatform and synthesize the nanoplatform with an efficient SDT effect. In this review, we initially summarize the probable SDT-based antibacterial mechanisms and systematically discuss the current advancement in different SDT-based nanoplatform (including nanoplatform for organic small-molecule sonosensitizer delivery and nanoplatform as sonosensitizer) for bacterial infection therapy. In addition, the biomedical applications of SDT-involved multifunctional nanoplatforms are also discussed. We believe the innovative SDT-based nanoplatforms would become a highly efficient next-generation noninvasive therapeutic tool for combating bacterial infection.